Nephrotic Syndrome in Pediatrics: A Case Report - Ratu Hanny Anggorowati; Huminsa Ranto Mourison Panjaitan; Andre Yusanto; Annisah, Rati (Scientific Journal of Pediatrics, 2023)
Introduction: The prevalence of childhood NS worldwide is approximately 16 cases per 100,000 children, with an incidence of two to seven per 100,000 children. Primary causes of NS include minimal change disease, focal segmental glomerulosclerosis, membranous nephropathy, genetic disorders, and secondary diseases associated with infections, drugs, and neoplasia; however, it can also be idiopathic. Case presentation: A 14-year-old male toddler weighing 39 kg with a 1-week history of swelling around the eyes and both legs and generalized body swelling. On physical examination, swelling was found in both lower legs (pitting type). Laboratory investigations showed protein in urine and reduced serum albumin (2.0 g/dL) with elevated lipid levels. Although a kidney biopsy could not be performed due to the economic problem of the family, a diagnosis of idiopathic nephrotic syndrome (NS) was made based on clinical and laboratory findings. Conclusion: Nephrotic syndrome in children includes dietary adjustments, administration of diuretics to reduce edema, and administration of immunosuppressants such as steroids to induce remission.